DISCRETIZATION CORRECTION OF PARTICLE STRENGTH EXCHANGE (DC PSE) OPERATOR FOR 2D STEADY STATE INCOMPRESSIBLE FLOW IN VELOCITY CORRECTION SCHEME - Humaedi, Ahmad
The methods of computational fluid dynamics are kept being developed to ob- tain an even more efficient program with accurate results. Navier-Stokes velocity- vorticity formulation has been studied and developed in several years. The conve- nient thing of using this formulation that the velocity and vorticity can be solved step by step, unlike the pressure-velocity Navier-Stokes formulation that have to be solved simultaneously. In this study, velocity-vorticity formulations are used in velocity correction scheme to analyse 2D steady incompressible flow.